Kerja Sama Australia dan Perancis dalam Proyek Pembuatan Kapal Selam - Cahyasari, Wulan; Suhermanto, Dedik Fitra (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2023)
This article discusses the collaborative relationship between Australia and France in the SEA 1000 Future Submarine Program. As a continent surrounded by vast oceans, Australia has a need to strengthen its navy. One of their security strategies is through the SEA 1000 Future Submarine project. Which aims to develop superior submarines. In carrying on this project, Australia decided to choose France as its partner. Precisely with the Naval Group, a French defense company. The purpose of this research is to analyze the reasons why Australia chose France as its partner in the SEA 1000 Future Submarine project. This research uses a descriptive research method, supported by journal literature, news, internet media, and official government websites. This research uses the rational choice theory and the concept of national security. The findings show that Australia chose France as its partner because the submarine design offered by France is more suitable for Australia’s needs. Economically, this collaboration can contribute to the development of Australia’s economy.